Neuroimaging of the Afferent Visual System - Mallery, Robert M.; Prasad, Sashank (Seminars in Neurology, 2012)
Neuroimaging studies provide a useful tool for the clinician evaluating a patient with visual loss. In this review, we discuss the use of magnetic resonance imaging (MRI), computed tomography (CT), orbital ultrasound, and optical coherence tomography (OCT) for evaluating causes of visual loss affecting the afferent visual system. The imaging characteristics of diseases affecting the optic nerve, orbit, sellar and parasellar region, optic tracts, and retrogeniculate visual pathways will be discussed.
Keywords: neuroimaging; neuro-ophthalmology; visual loss; optical coherence tomography (OCT); ultrasound